How can health systems make healthcare more accessible for populations experiencing homelessness? A realist and policy analysis - Siersbaek, Rikke (Trinity College Dublin. School of Medicine. Discipline of Public Health & Primary Care, 2022)
Problem Populations experiencing long-term homelessness and complex needs face difficulties accessing healthcare. Prior research has predominantly focused on the individual characteristics that contribute to those difficulties and how to improve access from that perspective. Meanwhile, there is a dearth of research focusing on how health systems can make services accessible for such vulnerable populations. The aim of this thesis is to explain health system factors that impact healthcare access among populations experiencing long-term homelessness and complex needs, and to propose ways to improve access. Methods Over three studies, one building on the next, the thesis examines the problem aim from different angles. The first study is a realist review, the second study a realist evaluation, and the third study a policy analysis. Data were collected via systematic and non-systematic literature searching, and via realist and semi-structured interviews. Realist approaches and policy analysis methods were used. Results Taken together, the three studies propose important health system factors which improve healthcare access. They found that high-level health system goals have to drive integrated, coordinated and multidisciplinary modes of providing healthcare. To support such delivery of care, services have to be adequately funded and resourced on an ongoing basis to enable practitioners to have the capacity to be flexible and adaptable in how they deliver care, and to build continuing relationships with patients. Appropriate levels of specialisation should be developed so everyone working in health services have a baseline knowledge of characteristics of vulnerable people and how to best engage with them, with some practitioners needing high levels of specialisation which can then be consulted and deployed when needed. The cultures in which healthcare is delivered must be inclusive and trauma-informed. Conclusion Health systems create the conditions in which healthcare encounters take place. This thesis has implications for the planning, funding, organising and evaluating of healthcare services in Ireland and internationally to make such services more accessible to populations experiencing long-term homelessness and complex needs.
APPROVED
Keywords: Health Policy; Homelessness; Health System; Realist Review; Realist Evaluation; Healthcare Access; Policy Analysis